Development of Sexual Education Animation Videos to Improve Sexual Understanding and Understanding of Forms of Sexual Harassment Behavior of Yogyakarta Elementary School Students - Yunita, Rosalia Nana; Wangid, Muhammad Nur (International Journal of Social Service and Research, 2024)
Sexual education has a crucial role in providing understanding to children about reproductive organs, prevention of sexual violence, and maintenance of intimate organs. This study aims to develop learning media in the form of sexual education animation videos to improve sexual understanding and understanding of forms of sexual harassment behavior in elementary schools. ADDIE research and development methods (Analysis, Design, Development, Implementation, and Evaluation) are used in this product development process. Needs analysis was conducted through interviews with guidance and counseling teachers, as well as classroom teachers in several elementary schools in Yogyakarta. The development phase involves material design, animation video creation, validation by media experts and material experts, as well as field trials. Evaluation is carried out to correct product deficiencies before they are widely implemented. The development results include animated sexual education videos that received "very decent" validation from media experts and material experts. Field trials involved grade V students with results that showed increased sexual understanding and understanding of forms of sexual harassment behavior in classes that used animated videos compared to control classes. The teacher's response to the media shows a high level of practicality. In conclusion, this sexual education animation video is considered feasible, practical, and effective in increasing students' understanding of sexual material and forms of sexual harassment behavior in elementary schools. This media is expected to help teachers in providing appropriate, interesting, and appropriate sexual education according to the needs of elementary school-age children.